Population-Level Human Secretor Status Is Associated With Genogroup 2 Type 4 Norovirus Predominance. (4th January 2020) - Arrouzet, Cory J; Ellis, Karen; Kambhampati, Anita; Chen, Yingxi; Steele, Molly; Lopman, Ben
Abstract: Background: Noroviruses are a leading cause of acute gastroenteritis. Genogroup 2 type 4 (GII.4) has been the dominant norovirus genotype worldwide since its emergence in the mid-1990s. Individuals with a functional fucosyltransferase-2 gene, known as secretors, have increased susceptibility to GII.4 noroviruses. We hypothesized that this individual-level trait may drive GII.4 norovirus predominance at the human population level. Methods: We conducted a systematic review for studies reporting norovirus outbreak or sporadic case genotypes and merged this with data on proportions of human secretor status in various countries from a separate systematic review. We used inverse variance-weighted linear regression to estimate magnitude of the population secretor-GII.4 proportion association. Results: Two hundred nineteen genotype and 112 secretor studies with data from 38 countries were included in the analysis. Study-level GII.4 proportion among all noroviruses ranged from 0% to 100%. Country secretor proportion ranged from 43.8% to 93.9%. We observed a 0.69% (95% confidence interval, 0.19–1.18) increase in GII.4 proportion for each percentage increase in human secretor proportion, controlling for Human Development Index. Conclusions: Norovirus evolution and diversity may be driven by local population human host genetics. Our results may have vaccine development implications including whether specific antigenic formulations would be required for different populations. Abstract : Using systematic literature review data, a positive population-level relationship was identified between the proportion of human secretor status in a population and predominance of the GII.4 norovirus genotype.